Slovenska leksikalna podatkovna zbirka - Gorjanc, Vojko (Jezik in slovstvo, 2005)
The article describes the idea of a lexical database for the Slovene language created on the basis of a corpus analysis. Starting points for the formation of the lexical database are based on experience gained during the trial phase while building a glossary for small dictionaries by DZS (i.e. the National Slovene Publishing House) with Slovene as the source language, and the corpus analysis as part of the research project entitled "Designing Corpus-based Dictionary and Grammar Descriptions for the Slovene language". The authors argue in favour of the creation of a lexical database claming that the exsisting dictionaries of the Slovene language are not a reflection of contemporary language, are methodologically outdated, and have never been consistent in their linguistic description without also being prescriptive. The proposed design for a lexical database enables the creation of different types of dictionaries; the outcome of the proposal is an inner hierarchic lexical description of contemporary Slovene, which can be obtained from the FIDA Reference Corpus of the Slovene Language.
Keywords: Slovene; slovenščina; leksikologija; lexicology; Corpus linguistics; korpusno jezikoslovje; FIDA; zbirke besedil